Advances in local and systemic drug delivery systems for post-surgical cancer treatment. Issue 37 (25th August 2020) - Aquib, Md; Juthi, Ajkia Zaman; Farooq, Muhammad Asim; Ali, Manasik Gumah; Janabi, Alhamzah Hasan Waheed; Bavi, Sneha; Banerjee, Parikshit; Bhosale, Raghunath; Bavi, Rohit; Wang, Bo
Abstract : Graphical representation of local and systemic drug delivery systems. Abstract : Surgery is considered to be the favored approach for the treatment of most solid tumor malignancies. The quality of life among cancer patients has significantly improved due to advancements in instrumentation and surgical techniques; however, the recurrence of tumors and metastasis after operation remains challenging and results in a decreased quality of life and an increase in the mortality rate. Therefore, there is a need to explore applicable approaches to eradicate the circulating tumor cells and any residual tumor at the surgical site to inhibit the recurrence of the tumor and reduce the threat of distant metastasis. Recently drug delivery systems have been used to deliver immunotherapy or chemotherapy agents, which could augment the efficacy of surgical resection. In this review, we have summarized the efficacy and the recent progress of controlled drug delivery systems based approaches for post-surgical cancer treatment. Clinical translation challenges and opportunities have also been discussed.